Sistema MES (manufacturing execution system): estudo das vantagens da aplicação nas indústrias - Hirai, Gabrielle Zanetti (2023)
With the increase in market competitiveness, the search for increased production efficiency (OEE) along with cost reduction, industries increasingly need reliable and fast data for strategic decision making, both for solving problems in the production line and for business directions in the corporate area. Aiming at this scenario, data from the production line need to reach systems such as ERP and production management, assertively and already treated. However, these are not able to receive data from the shop floor directly, só there are software that connect level 1 data (production line) to level 4 planning systems (ERP, CRM, among others). The objective of this work is to carry out an analysis of the MES system (Manufacturing Execution System) and its advantages when applied in industries. The research was focused on the MES system together with the ERP system (SAP), when used in industries that work with batch production.